Health Care Workers’ Use of Electronic Hospital Information System and Their Computer Literacy at the Outpatient Department in District General Hospital Trincomalee in Sri Lanka - Jayawardena, D.B.A.S.; Wickramasinghe, S.C.; Wimalaratne, S.R.U. (Department of Computer Science Faculty of Applied Sciences University of Sri Jayewardenepura, 2016)
Objectives: To describe the use of Electronic Hospital Information System (EHIS) by the staff, to assess the competency of them to handle the EHIS and to assess the computer literacy among health care workers at the Out Patient’s Department(OPD) in District General Hospital (DGH) Trincomalee. Study design: A cross sectional descriptive study. A competency assessment test and a self administered questionnaire were used. Participants: All the staff members operating the EHIS at the OPD in DGH Trincomalee. Results: Regarding the general use of the EHIS medical officers (100%) used the EHIS to write prescriptions,(>70%)to get the patient’s socio-demographic details, enter patient’s history to retrieve previous medical records, to obtain what drugs available and what drugs out of stock at the outdoor pharmacy, for notification of diseases and used less frequently to get the laboratory reports (50-70%). The system was used for 17 tasks out of 20 tasks and most unused tasks were writing the diagnosis according to the ICD-10. Nurses and attendants used the system less than half of the tasks for which the system was functional. The pharmacists use of the system was optimal. Overall respondents’ competency of using the system was high (>80%). Conclusions: Majority of staff members had low level of computer literacy. Majority of them used the system successfully. Recommendations: To strengthen the training program, combat several constraints and upgrade the system, provide digital X-ray imaging and download them to CDs and improved to write the diagnosis according to the ICD-10.
Keywords: Electronic Hospital Information System, Multi Disease Surveillance, Computer Literacy.